The Effect of Price and Promotion on Purchase Decisions That Have an Impact on Consumer Loyalty at PT. Sometech Indonesia in Jakarta - Dede Abdurohman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of price and promotion on purchasing decisions that have an impact on consumer loyalty at PT Sometech Indonesia in Jakarta. The method used is explanatory research with a sample of 98 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that the price has a significant effect on purchasing decisions by 36.9%, hypothesis testing obtained a significance of 0.000 <0.05. Promotion has a significant effect on purchasing decisions by 41.8%, hypothesis testing obtained a significance of 0.000 <0.05. Price and promotion simultaneously have a significant effect on purchasing decisions by 50.1%, hypothesis testing obtained a significance of 0.000 <0.05. Purchase decisions have a significant effect on consumer loyalty by 32.0%, hypothesis testing obtained a significance of 0.000 <0.05.